Menelisik Kontribusi Ayah dalam Mengajarkan Kemandirian pada Anak - Kosma Manurung (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2022)
Independence is very important for a child because independence fosters a sense of responsibility for children, independence bears joy, is closely related to children's emotional social intelligence, and independence contributes well to their future success. Judging from the position, closeness, and authority they have, fathers are considered the most appropriate in teaching this independence. Therefore, the active involvement of fathers is needed and expected. The research of this article is intended to explore the role that fathers can give in order to maximally teach independence to their children. By choosing a qualitative method with a description approach and support from a literature review, it is hoped that it can provide a maximum picture and be able to be accountable academically regarding independence in the biblical picture, the urgency of independence for children both now and in their future, as well as the contribution of fathers in teaching independence. It is concluded that fathers can contribute maximally in teaching independence to children when making it a habit for children, positioning themselves as companions in the learning process, being carried out with sensitivity and being a role model in terms of independence. AbstrakKemandirian sangat penting bagi seorang anak karena kemandirian menumbuhkan rasa tanggung jawab anak, kemandirian berbuah kegembiraan, terkait erat dengan kecerdasan sosial emosional anak, serta kemandirian bersumbangsih baik pada kesuksesannya di masa depan nanti. Menilik posisi, kedekatan,dan otoritas yang dimilikinya, para ayah dirasa paling tepat dalam mengajarkan kemandirian ini. Maka dari itu keterlibatan aktif para ayah sangat dibutuhkan dan diharapkan. Penelitian artikel ini dimaksudkan ingin menelisik peran yang para ayah bisa berikan agar maksimal mengajarkan kemandirian pada anak. Dengan memilih metode kualitatif dengan pendekatan deskripsi dan sokongan dari kajian literatur diharapkan bisa memberikan gambaran yang maksimal serta mampu dipertanggung jawabkan secara akademik terkait kemandirian dalam gambaran Alkitab, urgensi kemandirian bagi anak baik itu di masa kini ataupun di masa depan mereka, juga kontribusi ayah dalam mengajarkan kemandirian. Disimpulkan bahwa para ayah dapat berkontribusi maksimal dalam mengajarkan kemandirian pada anak ketika menjadikannya sebagai pembiasaan bagi anak, memposisikan dirinya sebagai pendamping dalam proses belajar, dilakukan dengan kepekaan dan menjadi role model dalam hal kemandirian.